(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Since changes in tissues and organs in aseptic inflammation have not been sufficiently studied, the purpose of this study was to determine the specific morphological changes that develop in the lymph nodes of the human body in aseptic inflammation. In aseptic inflammation, swelling increases around the lymph nodes, their sinusoids expand, and their parenchyma atrophies. In the parenchyma of the lymph nodes, morphofunctional zones are not distinguishable, and the stroma atrophies with collapse, sclerosis, and reticulosis.